KNOWLEDGE LEVEL OF ACEHNESE'PREGNANT WOMEN TOWARD PREECLAMPSIA IN COMMUNITY HEALTH CENTER IN BANDA ACEH, INDONESIA - Dewi Hermawati; Ela Safira (Fakultas Keperawatan-Universitas Syiah Kuala, 2021)
Preeclampsia is the second leading cause of death in the world after bleeding problem in pregnancy and childbirth course. In Indonesia, approximately 305 deaths of women from 100.000 live births occurred with preeclampsia as one of causes. Knowledge of preeclampsia is very important to be known by women for increasing their alertness and ability in caring pregnancy as well as taking preventive measures of preeclampsia. This study aims to identify the level of knowledge of pregnant women toward preeclampsia in working area of community health center in Banda Aceh. This is a descriptive exploratory research with a cross sectional design. The data collection using a questionnaire that is distributed through google form which covered definition, risk factors, complications and prevention of preeclampsia and analyzed with computer software. The result of study showed 56 (52.0%) of respondents had a good knowledge of preeclampsia, 32 (30.0%) of respondents had a sufficient knowledge of preeclampsia and 20 (18.0%) of respondents had a less knowledge of preeclampsia with a total of 108 respondents of this study. The study also revealed as many as 45 (41.7%) respondents had a sufficient knowledge about definition of preeclampsia and 54 (50.0 %), 56 (51.9%) and 76 (70.4%) of respondents had a good knowledge of risk factors, complications, and prevention of preeclampsia, respectively. It is hoped that health professionals will always provide continuous preeclampsia education that further increases ability of pregnant women in caring pregnancy without complication from preeclampsia.